Economic Exploitation of Children in The Urban Context: a Case Study of Palembang City - Hana Pertiwi; Atika Atika; Muhammad Abdillah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
This article aims to examine children as victims often exploited in the social reality of society. The study is conducted to observe how children are utilized as instruments to meet economic needs, primarily by their parents. Additionally, this investigation seeks to examine, analyze the causative factors, and explore the implications resulting from economic exploitation of children. The approach in this paper is descriptive-qualitative, utilizing a library research method with readings and searches on the Google search engine related to